Reluctant Feminists in German Social Democracy, 1885-1917 - Quataert, Jean H. (Jean Helen), 1945- (Book collections on Project MUSE., 1979)
Examining the convergence of socialism and feminism in the German labor movement around the turn of the century, Jean Quataert probes the competing identities and loyalties of class and sex and the problems their adherents faced in reconciling the two. By focusing on the women's movement in particular, she expands our understanding of the German Social Democratic subculture and shows that socialist feminism was far more important than has been recognized heretofore.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.